Strengthening the genomic surveillance of Francisella tularensis by using culture-free whole-genome sequencing from biological samples - Isidro, Joana; Escudero, Raquel; Luque-Larena, Juan José; Pinto, Miguel; Borges, Vítor; González-Martín-Niño, Rosa; Duarte, Sílvia; Vieira, Luís; Mougeot, François; Vidal, Dolors; Herrera-Rodríguez, Daniel; Rodríguez-Pastor, Ruth; et al. (Frontiers in Microbiology, 2024)
Francisella tularensis is a highly infectious bacterium that causes the zoonotic disease tularemia. The development of genotyping methods, especially those based on whole-genome sequencing (WGS), has recently increased the knowledge on the epidemiology of this disease. However, due to the difficulties associated with the growth and isolation of this fastidious pathogen in culture, the availability of strains and subsequently WGS data is still limited. To surpass these constraints, we aimed to implement a culture-free approach to capture and sequence F. tularensis genomes directly from complex samples. Biological samples obtained from 50 common voles and 13 Iberian hares collected in Spain were confirmed as positive for F. tularensis subsp. holarctica and subjected to a WGS target capture and enrichment protocol, using RNA oligonucleotide baits designed to cover F. tularensis genomic diversity. We obtained full genome sequences of F. tularensis from 13 animals (20.6%), two of which had mixed infections with distinct genotypes, and achieved a higher success rate when compared with culture-dependent WGS (only successful for two animals). The new genomes belonged to different clades commonly identified in Europe (B.49, B.51 and B.262) and subclades. Despite being phylogenetically closely related to other genomes from Spain, the detected clusters often enrolled other countries. A comprehensive phylogenetic analysis, integrating 599 F. tularensis subsp. holarctica genomes, showed that most (sub)clades are found in both humans and animals and that closely related strains are found in different, and often geographically distant, countries. Overall, we show that the implemented culture-free WGS methodology yields timely, complete and high-quality genomic data of F. tularensis, being a highly valuable approach to promote and potentiate the genomic surveillance of F. tularensis and ultimately increase the knowledge on the genomics, ecology and epidemiology of this highly infectious pathogen.